(untitled) (Global Journal of Management and Business Research, 2014)
Organizational efficiency is still important to planning because it enables plans that are possible to achieve profitability. Efficiency measure of how well or how productively resources are used to achieve a goal. Banking sector is important factor for economic development. The study is also aimed at finding the effect of changes in efficiency levels on profitability of banking in Sri Lanka. The study covered banking sector in Sri Lanka over a period of past 5 years from 2008 to 2012. Correlation and regression analysis were used in the analysis and findings suggest that there is a significant relationship exists between efficiency and profitability. However, the findings of this paper are based on a study conducted on the banking sector in Sri Lanka. Results of this study found that the Sales to Total Asset (SA/TA) is significantly correlated with Operating Profit Margin (OPM) and Return on Equity (ROE). At the same time SA/TA and Operating Expenses to Total Assets (OPE/TA) and Loan to Total Assets (LO/TA) are significantly correlated with Net profit Margin (NPM).